Survival and failure modes of the Compress® spindle and expandable distal femur endoprosthesis among pediatric patients: A multi‐institutional study. Issue 1 (16th September 2022) - Tanaka, Kara S.; Andaya, Veronica R.; Thorpe, Steven W.; Gundle, Kenneth R.; Hayden, James B.; Duong, Yee‐Cheen; Avedian, Raffi S.; Mohler, David G.; Morse, Lee J.; Zimel, Melissa N.; O'Donnell, Richard J.; Fang, Andrew; et al.
Abstract: Background: Expandable endoprostheses can be used to equalize limb length for pediatric patients requiring reconstruction following large bony oncologic resections. Outcomes of the Compress® Compliant Pre‐Stress (CPS) spindle paired with an Orthopedic Salvage System expandable distal femur endoprosthesis have not been reported. Methods: We conducted a multi‐institutional retrospective study of pediatric patients with distal femoral bone sarcomas reconstructed with the above endoprostheses. Statistical analysis utilized Kaplan–Meier survival technique and competing risk analysis. Results: Thirty‐six patients were included from five institutions. Spindle survivorship was 86.3% (95% confidence interval [CI], 67.7–93.5) at 10 years. Two patients had a failure of osseointegration (5.7%), both within 12 months. Twenty‐two (59%) patients had 70 lengthening procedures, with mean expansions of 3.2 cm (range: 1–9) over 3.4 surgeries. The expandable mechanism failed in eight patients with a cumulative incidence of 16.1% (95% CI, 5.6–31.5) at 5 years. Twenty‐nine patients sustained International Society of Limb Salvage failures requiring 63 unplanned surgeries. Periprosthetic joint infection occurred in six patients (16.7%). Limb preservation rate was 91% at 10 years. Conclusions: There is a high rate of osseointegration of the Compress® spindle among pediatric patients when coupled with an expandable implant. However, there is a high rate of expansion mechanism failure and prosthetic joint infections requiring revision surgery. Level of evidence: Level IV, therapeutic study.